Applying the blue economy on the Mampie coast: Geobag and mangrove solutions for abrasion - Putera, Alexander Kurniawan Sariyanto; Isdaryanti, Isdaryanti; Saudi, Akbar Indrawan; Kamal, Kamal; Ishaq, Ishaq; Nurhalizah, Nurhalizah; Yusuf, Muhammad; Mandrigau, Tiara Septia; Fatmawati, Fatmawati (Community Empowerment, 2025)
Coastal abrasion at Mampie Beach, West Sulawesi, poses a serious threat to community livelihoods and biodiversity. This community-based program aimed to implement Blue Economy principles by integrating eco-technology and mangrove adoption to mitigate abrasion while empowering the local community at Rumah Sahabat Penyu. The methods included the installation of 60 geobags, planting 300 Rhizophora mangrove seedlings, and training in mangrove-based soap making as a sustainable livelihood initiative. Evaluation results showed that 100% of the geobags remained intact and the mangrove survival rate reached 80% (though 20% were damaged by plastic debris, large wood, and human activities). Furthermore, 23 participants successfully learned the mangrove-based soap-making process, enhancing environmental awareness and economic resilience. This program confirms the effectiveness of combining eco-technology and community participation in coastal protection and sustainable livelihood development. Further monitoring is recommended to evaluate the long-term performance of geobags and mangrove survival during peak abrasion seasons.